Correlation between Serum Adiponectin Levels and Forced Expiratory Volume in 1 Second (FEV1) Scores in Asthmatic Patients - Mulyadi Subarjo; Muhammad Amin (Jurnal Respirologi Indonesia, 2019)
Background: The adipokine is a group of protein secreted from the adipose tissues, producing among other the anti-inflammatory adiponectin. Serum adiponectin concentration decreases at asthma and has reverse correlation with the worse prognosis. Adiponectin correlation with asthmatic patients currently is still a controversy, though adiponectin and its receptor are expressed within the cells of airway. The purpose of this research is to verify the correlation between adipokine, especially the role of the adiponectin in influencing airway obstruction degree measured under FEV1 scores in asthmatic patients. Methods: Observational analytical research with cross section design in Policlinic of Asthma/PPOK Regional General Hospital of Dr. Soetomo Surabaya from March to April 2018 was conducted to 40 qualified inclusion and exclusion asthmatic patients as the research samples. There were spirometry and venous blood tests to measure the FEV scores and the serum adiponectin levels respectively, using the Sandwich Enzyme Linked Immuno Sorbent Assay (ELISA) method. Results: No significant correlation between FEV towards adiponectin levels (r = 0,174; 95% CI = -0,145 – 0,461; P = 0,283). No significant ratio different between FEV1 scores towards adiponectin group (P = 0,885). The highest FEV1 average was found on the lower adiponectin group. No significant different between serum adiponectin levels on the mild / moderate / severe obstruction degree groups (P = 0,259). The highest serum adiponectin levels in obstruction degree groups (ADP = 57,08 ng/ml) was found in the mild, followed with the moderate (ADP = 49,72 ng/ml), and severe groups (ADP = 45,58 ng/ml). Conclusion: No significant correlation between FEV1scores and serum adiponectin levels in asthmatic patients. But there was parallel correlation trend, such as the decrease of serum adiponectin levels, and of the FEV scores, though it was insignificant. (J Respir Indo 2019; 39(2): 113-20)